Comparative Evaluation of Postoperative Incisional Negative Pressure Wound Therapy with Conventional Dressings in Patients of Proximal Tibia Fracture Managed by Dual Plating - Pranav Kothiyal; Kunal Vij; Puneet Gupta (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: High-velocity injuries of the tibial plateau managed by operative intervention are often complicated by surgical site infections and delayed wound healing. Incisional negative pressure wound therapy (NPWT) is an established technique for the management of wound complications and is also being used nowadays for early healing of uncomplicated postoperative wounds. Materials and Methods: We conducted this study to compare the effectiveness of NPWT over conventional dressing methods by creating two groups of patients with tibial plateau fractures managed by plating. Postoperatively, NPWT was applied to one group and the other group was followed up with routine conventional dressings. Results: A total of 88 patients were included in the study, and it was found that the rate of minor and major wound site complications was more in the group of patients managed by conventional dressing. Conclusion: With our study, we concluded that in high-velocity proximal tibia fractures with a lot of soft-tissue traumas, incisional NPWT is well tolerated and has shown a definitive advantage in preventing wound-related complications as compared to regular conventional dressing.